Comparison of GnRH agonist and hCG for priming in vitro maturation cycles in cancer patients undergoing urgent fertility preservation - El Hachem, Hady (PLoS One, 2018)
In vitro maturation (IVM) of oocytes retrieved at germinal vesicle or Metaphase I stage, followed by vitrification of Metaphase II (MII) oocytes, has recently emerged as an option for urgent fertility preservation (FP). Priming is usually achieved with an injection of hCG, 10,000 IU, 36 hours before retrieval. This study aimed to assess a new method of priming, using GnRH agonists, and compare it to hCG, in cancer patients undergoing urgent FP. From 2009 to 2015, 373 cancer patients underwent MII oocyte cryopreservation after IVM cycles primed either with GnRHa (triptorelin 0.2 mg) (n = 138) or hCG (10,000 IU) (n = 235). Patients’ characteristics were comparable between the two groups. The number of COC retrieved was significantly higher in the GnRHa group (9.1 ± 6.8 versus 7.7 ± 5.5 oocytes, p = 0.04). However, the maturation rates (59 ±25% versus 64 ±26%, p = 0.07, respectively), and the total number of MII oocytes frozen (5.2 ±4.2 versus 4.9 ±4.0, p = 0.6, respectively) were similar between the GnRha and hCG groups. We did not find any difference between GnRHa and hCG priming for IVM. GnRHa priming is more physiological since it stimulates endogenous FSH and LH activity, and is well suited for FP in hormone-sensitive cancers and urgent cases.